2021
DOI: 10.1097/olq.0000000000001411
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Pooled 3 Anatomic Site Testing for Chlamydia trachomatis and Neisseria gonorrhoeae Among Men Who Have Sex With Men and Transgender Women

Abstract: Background: Although molecular testing for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) is highly sensitive, the cost can be prohibitive. Those high costs are amplified when the recommended screening approach is used, which requires separate testing of specimens from 3 anatomic sites (rectal, pharyngeal and urogenital). Although individual molecular testing is standard of care, pooled testing may offer a costsaving alternative.Methods: Using the Xpert® CT/NG assay (Cepheid, Sunnyvale, CA) we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…24,26,27 Regarding the evaluation of two syphilis RDTs, our study demonstrated 100.0% agreement between the two readers, suggesting that the tests were easy to interpret which is consistent with a study in Burkina Faso which has also shown that syphilis RDTs have solid operational characteristics and easy-tointerpret results. 11 The overall prevalence syphilis infection of 10.5% is relatively low compared to a 2018 study in Thailand (12.0%) 25 but remains high compared to pooled prevalence of syphilis among MSM globally (7.5%) 3 and in Asia (9.9%). 28 The high prevalence of syphilis infection among our study participants could be explained by this study being conducted at a tertiary center offering STI treatment.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…24,26,27 Regarding the evaluation of two syphilis RDTs, our study demonstrated 100.0% agreement between the two readers, suggesting that the tests were easy to interpret which is consistent with a study in Burkina Faso which has also shown that syphilis RDTs have solid operational characteristics and easy-tointerpret results. 11 The overall prevalence syphilis infection of 10.5% is relatively low compared to a 2018 study in Thailand (12.0%) 25 but remains high compared to pooled prevalence of syphilis among MSM globally (7.5%) 3 and in Asia (9.9%). 28 The high prevalence of syphilis infection among our study participants could be explained by this study being conducted at a tertiary center offering STI treatment.…”
Section: Discussionmentioning
confidence: 86%
“…The prevalence of syphilis infection was assumed to be 12.0% based on a previous study. 25 Accepting a marginal error of 15%, 187 participants were required. To account for an estimated 10% of insufficient specimens, we included 200 participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our search yielded a total of 71 publications, 31 of which were in duplicate from another database. Fourteen met our inclusion criteria, [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and 26 were excluded because they were not studies evaluating pooled testing, were overlapping data sets, or were a commentary, meta-analysis or review article (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…While testing multiple anatomical sites separately is ideal, increase of cost and/or workload related to this testing strategy would be one of the major concerns. To respond to this concern, several studies have investigated the diagnostic accuracy of pooled specimens from the three anatomical sites (urethra, pharynx and rectum) to detect CT and NG 8–18. Among these studies, the ex-ante pooling approach8–10 12 14 17 or the ex-post11 13 15 16 18 were used.…”
Section: Introductionmentioning
confidence: 99%
“…To respond to this concern, several studies have investigated the diagnostic accuracy of pooled specimens from the three anatomical sites (urethra, pharynx and rectum) to detect CT and NG 8–18. Among these studies, the ex-ante pooling approach8–10 12 14 17 or the ex-post11 13 15 16 18 were used. Ex-ante pooling is placing the original single-site specimens in a tube with transport media, while ex-post pooling is making a pool of the transport media from both anorectal and oropharyngeal specimens and the urine.…”
Section: Introductionmentioning
confidence: 99%